The Use of Diagnosis-Related Group-Based Reimbursement in the Czech Hospital Care System - Kotherová, Zuzana; Caithamlová, Martina; Nemec, Juraj; Dolejšová, Kateřina (International journal of environmental research and public health, 2021)
(1) Background: Diagnosis-Related Groups (DRG), one possibility of a hospital payment system, are currently used in most European countries. Introduced to the Czech system in the 1990s, the DRGs are currently used mainly for care reporting and partly for reimbursement. According to most experts, the use of DRG remain controversial. The goal of this paper was to study the effects of the current Czech DRG system on hospitals financing and, on this basis, to propose possible changes to the reimbursement mechanism in the Czech Republic. (2) Methods: Qualitative research methods were used for evaluating DRG mechanisms of application in three selected healthcare establishments in the CR in the period of 2012-2018. (3) Results: Our study shows that the current implementation of the DRG system is set up in a way that is very similar to traditional flat rates and is unlikely to yield major positive effects of the DRG mechanism, such as predictability of payments for hospitalisation cases, care quality and efficiency and transparent financing. (4) Conclusions: Based on our results, deep systemic change of the reimbursement mechanism in the Czech Republic is necessary. We propose five partial measures leading to the cultivation of the Czech DRG.
Keywords: Czech Republic; Humans; Reimbursement Mechanisms; hospital economy; dávkové mechanismy; nemocnice; DRG; Evropa; Česká republika; Diagnosis-Related Groups; Europe; Hospitals; lidé; klasifikační systém DRG